Unilateral granulomatous conjunctivitis in a pregnant retroviral positive woman on HAART (Bangladesh Journal of Medical Science, 2021)
Ocular sporotrichosis is a relatively rare infection. We report a case of right ocular sporotrichosis in a 35 year-old pregnant woman at 30-week period of gestation with underlying retroviral disease on highly active antiretroviral therapy (HAART). She presented with one month history of unilateral eye redness and itchiness. Her symptoms persisted despite treatment for conjunctivitis. She was subsequently referred to ophthalmology clinic and a diagnosis of ocular sporotrichosis was made based on the culture of excised conjunctival tissues. Her symptoms improved after she was treated with fluconazole eye drops and intralesional amphotericin B. This case highlights the importance of early referral to ophthalmology in the case of unilateral eye redness in a high risk patient with history of exposure to infected cat prior to presentation.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.453-455